STUDY ON ADSORPTION OF Cd(II) BY CHITOSAN-ALUMINA - Darjito Darjito; Danar Purwonugroho; Siti Nasirotun Nisa (Universitas Gadjah Mada, 2006)
One techniques to reduce the concentration of heavy metal Cd(II) in aqueous solution is adsorption by chitosan. To modify the surface textures and expose the active binding sites, composite biosorbent has been prepared by coating chitosan onto alumina. The aims of this research were to identify the functional group of chitosan-alumina, to characterize adsorption of Cd(II) by using chitosan-alumina adsorbent including optimum pH, optimum agitation time, and to determine the adsorption capacity of the adsorbent. The functional group of chitosan-alumina was identified by infrared spectrophotometer. Determination of the optimum condition was carried out at 40 ppm Cd(II), 125 rpm and 0,1 g adsorbent. Calculation of adsorpted Cd(II) based on its concentration in aqueous phase before and after adsorption process. The concentrations of Cd(II) in aqueous phase after adsorption process were determined by using Atomic Absorption Spectroscopy (AAS). Identified functional groups of chitosan-alumina were -OH (3466.39 cm-1), -NH amine (1625.15 cm-1), C=O (1703.30 cm-1), and Al-O (1302.07 cm-1). The optimum pH was reached at pH 7, optimum agitation time at 15 minutes, and adsorption capacity of chitosan-alumina was 15.35 ± 0.05 mg/g.